Acetabular dysplasia and osteoarthritis of the hip in elderly white women. Issue 10 (1st October 1997) - Lane, Nancy E; Nevitt, Michael C; Cooper, Cyrus; Pressman, Alice; Gore, Robert; Hochberg, Marc
Abstract : OBJECTIVES: To examine the association of acetabular dysplasia and osteoarthritis (OA) of the hip among elderly white women. METHODS: Pelvic radiographs from a sample of 165 white women aged 65 and above with radiographic hip OA and 88 white women aged 65 and above without radiographic changes of hip OA were read for evidence of acetabular dysplasia by a single trained investigator. Acetabular dysplasia was assessed using measurements of the centre edge angle and the acetabular depth, which are both reduced in this condition. Odds ratios for the association between acetabular dysplasia and hip OA were estimated using logistic regression analysis. RESULTS: Fourteen (3.4%) hips had a centre edge angle < 25°, 46 (11.2%) hips had an acetabular depth of < 9 mm, and 54 (13.2%) hips had acetabular dysplasia defined as either of the above. Hips with OA had a small, but not statistically significant, increased prevalence of abnormal centre edge angle (odds ratio: 1.43; 95% confidence intervals: 0.46, 4.46), abnormal acetabular depth (1.47; 0.78, 2.77) and acetabular dysplasia (1.33; 0.74, 2.40). CONCLUSION: These results do not support the hypothesis that mild acetabular dysplasia accounts for a substantial proportion of hip OA in elderly white women. A study with a much larger sample size would be required to rule out a weak association between dysplasia and hip OA of the magnitude actually observed in our study.